2023
DOI: 10.1590/0034-7167-2022-0475
|View full text |Cite
|
Sign up to set email alerts
|

Primary Health Care assessment in the COVID-19 pandemic from physicians’ and nurses’ perspective

Abstract: Objectives: to assess the operationalization of Primary Health Care in the COVID-19 pandemic, according to Primary Care Assessment Tool: PCATool-Brasil attributes, from physicians’ and nurses’ perspective. Methods: a cross-sectional study, carried out with 99 physicians and nurses from Basic Health Units in a state in northeastern Brazil, with the aid of the adapted instrument PCATool-Brasil. Results: Essential Score was classified as high performance (6.6) and General Score as low performance (6.5). First C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…COVID-19 rapidly spread worldwide and was declared a pandemic in early 2020. In Brazil, due to its vast geographical expanse and significant economic, social, and cultural disparities, the impact of the disease was unevenly manifested across the country [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 rapidly spread worldwide and was declared a pandemic in early 2020. In Brazil, due to its vast geographical expanse and significant economic, social, and cultural disparities, the impact of the disease was unevenly manifested across the country [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In the current year, the lethality rate is 7.2%, while the country’s overall lethality rate is 2.8%. Epidemiological Weeks 20 and 21, which took place from May 16 to 29, 2021, showed that in 2020, 544 deaths of pregnant and postpartum women were reported, while by May 2021, there were already 911 confirmed deaths, more frequently observed in pregnant women ( 2 - 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true in the third trimester of gestation, where there may be a need to anticipate delivery. This greater susceptibility characterizes pregnant women as a risk group for SARS-CoV-2 infection ( 4 - 6 ) .…”
Section: Introductionmentioning
confidence: 99%